2022
DOI: 10.1155/2022/5005263
|View full text |Cite
|
Sign up to set email alerts
|

Fault Identification of Low-Speed Hub Bearing of Crane Based on MBMD and BP Neural Network

Abstract: As the key bearing part of the crane, the low-speed hub bearing of the crane exists in special working conditions of low-speed and alternating heavy load. It is difficult to extract its fault characteristics accurately by existing analysis methods. The main idea of the broadband mode decomposition (BMD) method previously proposed is to search in the association dictionary library containing broadband and narrowband signals. However, when it is applied to the broadband signals interfered by strong noise, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Recently, intelligent assessment methods based on machine learning [17] [18] have been used for crane safety assessments. For instance, Guo et al [19] developed a fault identification model for low-speed crane hub bearings based on wideband mode decomposition and a backpropagation neural network. However, machine-learning methods require numerous learning samples and are primarily used for fault diagnosis and identification of lifting mechanical parts.…”
Section: Literature Review On Crane Safety Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, intelligent assessment methods based on machine learning [17] [18] have been used for crane safety assessments. For instance, Guo et al [19] developed a fault identification model for low-speed crane hub bearings based on wideband mode decomposition and a backpropagation neural network. However, machine-learning methods require numerous learning samples and are primarily used for fault diagnosis and identification of lifting mechanical parts.…”
Section: Literature Review On Crane Safety Evaluationmentioning
confidence: 99%
“…In Table V, the decision matrix for hazards is presented as R. The risk factors (O, S, and D) were considered as cost indices. In the next step, the decision matrix of the hazards was normalized using (19). For example, the normalized rating for H1 for risk factor S is given as follows.…”
Section: ) Normalize Decision-making Matrixmentioning
confidence: 99%
“…With the development of machine learning, BP neural network, SVM, and DBN are applied to intelligent fault classification of bearings [18][19][20]. Guo et al [21] extracted fault information using the modulated broadband mode decomposition method. Inputting fault information into BP neural network to diagnose the fault of low-speed hub bearing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some scholars proposed a damage prediction method based on the "natural frequency change square ratio," which achieved better results than using the frequency alone. Guo et al [3] used a BP neural network combined with a modulated broadband mode decomposition (MBMD) method to monitor crane-bearing parts and concluded that the BP neural network has good performance in feature extraction and fault recognition. Rastin et al [4] presented a novel two-stage technique based on generative adversarial networks (GANs) for unsupervised structural health monitoring and damage identifcation.…”
Section: Introductionmentioning
confidence: 99%